The economics of vocational training : past evidence and future considerations - Metcalf, David H. (Washington, D.C., U.S.A. : World Bank, 1985)
This paper presents a partial survey of the literature on the economics of vocational training to draw some lessons for evaluations and indicates how such evaluations may be undertaken using data on pay, inputs and outputs
Includes bibliographical references: p. 143-150.
osc 05/03/2019
Loans
Keywords: Occupational training; Vocational education